Analysis of handover interruption in vertical handover procedures based on 3GPP standard. (14th December 2021) - Shin, Sungjin; Han, Donghyuk; Cho, Hyoungjun; Chung, Jong-Moon
Applications which required real-time communications like mobile clouds, augmented reality, and voice over IP (VoIP) have significantly increased, and therefore the need to support seamless connectivity across overlaid heterogeneous networks are becoming more and more important. Handover interruptions (HI) may occur when mobile users move from the long-term evolution (LTE) to wireless local area network (WLAN) (or from WLAN to LTE) during active real-time applications. This paper analyses vertical handover (VHO) schemes and VHO procedures based on 3GPP for confirming interruption time.